Rancang Bangun Media Pembelajaran Pakaian Adat Sumbawa Berbasis Android - Susainanda, Riki; Esabella, Shinta (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Sumbawa Regency, West Nusa Tenggara Province (NTB) in eastern Indonesia is in great demand by local and international tourists. It is necessary to preserve diverse cultures, one of which is traditional clothing. Where the community still does not understand the traditional clothes of Sumbawa and the people tend to combine in dressing. This research aims to design an Android-Based Sumbawa Traditional Clothing Learning Media Application with the Waterfall method, which aims to produce web-based and android-based applications presented with visuals and text. The application presents Home, History, Clothing Categories and About features. The data collection methods carried out are observation, interview, and literature study methods. The application is built using the Waterfall method software development methodology, with the Laravel Framework, Flutter Software Development Kit, the Dart programming language and Visual Studio Code text editor as well as black box testing. The result of this research is the Sumbawa Traditional Clothing Learning Media Application.